(untitled) (CIPEEX, 2022)
Electricity is one of the most widely used forms of energy in the world, primarily generated by harnessing the energy potential of water in hydroelectric plants. However, it can also be generated in wind farms, thermal power plants, solar plants, nuclear plants, among others. Therefore, in Brazil, the generation of electricity through the photovoltaic process is extremely promising – solar generation in a clean, renewed, and sustainable way, as the country has an extensive territorial area with high levels of solar irradiation. In this sense, there are several research works involving the financial and technical reasons for the installation of photovoltaic plants. However, little is known or explored about the environmental, scientific, social, and architectural impacts/benefits, as well as the vision for studies and research on the installations of Photovoltaic Plants. Therefore, this work aims to analyze the energy efficiency and sustainability patterns of the UniEVANGÉLICA Photovoltaic Plant, and correlate them with the environmental benefits achieved through the generation of clean, renewable, and sustainable electricity. To this end, the following methodologies are being used: Theoretical Research – in order to understand the State of the Art and/or Scientometrics, the platforms Web Of Science, Science Direct, Scielo, Scopus, ACM, and others are being used; Practical Research - for conducting technical studies on the transmission of generated energy, quality of the generated energy, and efficiency of the system of this electric power generation system through the photovoltaic process, the Energy Efficiency Laboratory of UniEVANGÉLICA (LEEFoto) is being used. As expected results, it aims to generate knowledge in the area of management and energy efficiency of photovoltaic plants as well as validations of methodologies to assist in decision-making for the use of clean and sustainable electricity generation, with an emphasis on the generation indicators of the UniEVANGÉLICA Photovoltaic Plant and environmental indicators (solar radiation, wind speed, and climate changes) of the municipality of Anápolis-Goiás.